Generation of polarization-controllable low-frequency THz radiations from single-layer graphene using incommensurate two-color laser pulses - Guan, Zhong; You, Jiahao; Wang, Bincheng; Li, Xiaoyong; Wang, Guo-Li; Zhou, Xiao-Xin; Jin, Cheng (Frontiers in Physics, 2023)
We propose to combine a circularly polarized first-color laser with a linearly polarized secondcolor laser to control the polarization of THz radiations in the low-frequency region from single-layer graphene. We find that the THz ellipticity can be greatly adjusted by varying the wavelength of second color, and it can be slightly modified by varying the intensity ratio of two colors. We then show that the polarization direction of THz emissions can be dramatically changed by changing the phase difference between two colors. We also identify that the intensity, ellipticity, and polarization direction of THz wave can be changed simultaneously with the time delay between two colors. These can be understood by analyzing the electron currents, intensities of THz emissions in two orthogonal directions, and the phase difference between them. Our proposed scheme can be easily performed in the experiment based on the laser technology nowadays.